Recommendations for the Conduct, Reporting, Editing and Publication of Scholarly Work in Medical Journals - Article Editorial ("Paediatrician" Publishers LLC, 2017)
This is a Russian language translation of the ICMJE Recommendations for the Conduct, Reporting, Editing and Publication of Scholarly Work in Medical Journals. Updated in December 2016. This translation was prepared by V. Dengin with support from Media Sphera Publishing Group (academic editor Saygitov R.T., technical editors Solovova M.N., Shoshina M.N.). The ICMJE has not endorsed nor approved the contents of this translation. The official version of the Recommendations for the Conduct, Reporting, Editing and Publication of Scholarly Work in Medical Journals is located at www.icmje.org. Users should cite this official version when citing the document.